Menciptakan Kemandirian Batik Bekasi untuk UKM Batik di Pemerintah Kota dan Kabupaten Bekasi, Jawa Barat - Purwani Setyaningrum, Retno; Ekhsan, Muhamad; Fatchan, Muhammad (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
This Community Service (PkM) activity aims to create the independence of Bekasi Batik by introducing Pakem Batik Bekasi and the novelty of Bekasi Batik from batik batik in Indonesia, as well as independence as an entrepreneur who is able to increase the competitiveness and sustainability of his business. The method used is to provide digital marketing training, how to create content both in indonesian and english, business model canvas, AMO (Ability Motivation Opportunity), innovation and creativity, and branding. In addition to training, mentoring and coaching are also provided and the creation of the Bekasi Batik platform application, so that the promotion system is not only through exhibitions, but also online sales are usually carried out, namely through IG or other online media, but the creation of a platform application specifically about Batik and highlighting the novelty of Bekasi batik with other batik in Indonesia, even the creation of batik and ecoprint which are not only used for fashion but batik and ecoprint are poured into various handicrafts. Even made according to the consumption of the millennial and Z generations as the majority generation in Indonesia.